Thermal conductivity enhancement for CuO nanoflakes in oil‐based and oil blend‐based nanofluids. Issue 8 (11th March 2021) - Abutaleb, Ahmed; Imran, Mohd
Abstract: We report the synthesis and characterization of copper oxide (CuO) nanoflakes (Nflks) for thermal conductivity analysis. The synthesized Nflks were used for the preparation of oil‐based and oil blend‐based nanofluids. A dynamic light scattering study was carried out for aqueous suspension of CuO Nflks. The size distribution data show the two peaks emerged at 178.2 ± 31.77 nm and 861.7 ± 248.6 nm. The zeta potential was investigated, and the peak was observed at −46.4 ± 14.3 mV. The average thermal conductivity coefficients were calculated for mineral oil, sunflower oil, and oil blend, which were found to be 0.086, 0.105, and 0.099 W/mK, respectively. Furthermore, thermal conductivity enhancement was calculated, and the maximum percent enhancement was recorded for sunflower oil‐based nanofluid, which was found to be ~20.68% at 0.46 vol%. At similar vol%, the enhancement in thermal conductivity in oil blend‐based and mineral oil‐based nanofluids was found to be 16.14 and 15.73%, respectively. The oil‐based nanofluids are promising in electronics and modern computational devices to minimize the heating effect. Abstract : Copper oxide (CuO) nanoflakes (Nflks) were synthesized by the chemical coprecipitation method using copper salt and aqueous NaOH solution. Nflks were characterized by X‐ray diffraction, scanning electron microscopy, Fourier transform infrared, size distribution, and zeta potential. Nanofluids were prepared by dispersing CuO Nflks in sunflower oil, mineral oil, and oil blend (sunflower and mineral oil). Thermal conductivity enhancement was observed for each nanofluid against their respective base fluid.